2015
DOI: 10.1111/iju.12839
|View full text |Cite
|
Sign up to set email alerts
|

High neutrophil‐to‐lymphocyte ratio predicts poor clinical outcome in patients with castration‐resistant prostate cancer treated with docetaxel chemotherapy

Abstract: Objective: To evaluate the prognostic significance of the neutrophil-to-lymphocyte ratio in patients receiving chemotherapy with docetaxel for castration-resistant prostate cancer. Methods: A total of 57 castration-resistant prostate cancer patients treated between 2009 and 2014 were included in the present retrospective study. All patient data, including clinicopathological factors, were assessed. Univariate and multivariate Cox regression models were used to predict overall survival and progression-free surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…After full text assessment, 11 studies did not evaluate the relationship between NLR and survival separately, or failed to report the key data (HR, 95% CI, or P value). Thus, 14 studies with 16,598 PCa patients, 12,1931 which met our selection criterion, were eventually included in our research. They were all of high quality for our analysis by meta-analysis of observational studies in epidemiology assessment.…”
Section: Resultsmentioning
confidence: 99%
“…After full text assessment, 11 studies did not evaluate the relationship between NLR and survival separately, or failed to report the key data (HR, 95% CI, or P value). Thus, 14 studies with 16,598 PCa patients, 12,1931 which met our selection criterion, were eventually included in our research. They were all of high quality for our analysis by meta-analysis of observational studies in epidemiology assessment.…”
Section: Resultsmentioning
confidence: 99%
“…A summary of 15 recent studies investigating the prognostic role of NLR in PC is shown in Table . Six studies investigated the prognostic value of NLR in patients who underwent radical prostatectomy for PC; five studies evaluated the preoperative value, and the remaining studies evaluated postoperative values.…”
Section: Differential Blood Cell Markersmentioning
confidence: 99%
“…The cut‐off value for high versus low NLR varied from 3 to 5. Six studies showed that high pretreatment NLR was associated with poor survival in patients who received docetaxel chemotherapy for mCRPC . In addition to the role of pretreatment NLR, Lorente et al .…”
Section: Differential Blood Cell Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…The neutrophil-to-lymphocyte ratio (NLR) is one factor that has been widely reported to be a prognostic factor not only in prostate cancer but also in some solid cancers (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In addition, the NLR can be calculated easily from routine complete blood counts (CBCs) in peripheral blood samples (4,5).…”
Section: Introductionmentioning
confidence: 99%